Jocelyne Cesari, The awakening of Muslim democracy: religion, modernity, and the state - Shukri, Syaza Farhana Mohamad (International Institute of Advanced Islamic Studies (IAIS) Malaysia, 2015)
The book argues against the prevalent theory of modernisation and democratisation that the separation between state and religion should be the natural outcome of a modernising Islamic society, similar to the historical trajectory of the West as a liberal political system. Instead, the author shows through her meticulous work in the Middle East that to the contrary, Islam is further politicised in the region following the formation of nation-states because there is a lack of demarcation between Islam and the nation as an identity. The main tenet of the book is that â€œ[t]he use of Western secular techniques in law and constitutions created a strong connection between Islam and politics and contributed to the redefinition of Islam as a political norm in ways unknown under the Muslim empires.â€ (p. 7) It is this conflation between the religious and political self of Muslims in the early twentieth century that makes it difficult for state institutions to ignore the peopleâ€™s natural desire for a religious life and therefore political system. Although this conversation is far from new, the authorâ€™s argument is meant to rattle the prevalent discourse so that we can find a way forward for democratic Muslims without having to undermine their experience or reality.